Characterizing Competing Viewpoints in Stormwater Governance: An Urban Honolulu Case Study - Arik, Aida D. (Frontiers in Sustainable Cities, 2022)
Loss of community trust in government through poorly executed planning processes can be challenging to recover and requires extensive trust-building efforts, especially through authentic dialogue. This paper examines stormwater management priorities expressed by community leaders and residents, educators, industry professionals, and water managers. It uses Q-methodology, a mixed-method approach, to understand prevalent narratives around stormwater management that comprise the public discourse. The purpose of this research is to elucidate points of agreement and disagreement in the context of a contentious flood risk management project. In total, 18 participants ranked an identical set of 25 idea statements relative to one another. Through principal component analysis, I identify four distinct narratives that prioritize different aspects of stormwater management objectives. The narrative analysis shows broad agreement that decentralized, soft infrastructure (e.g., green infrastructure) should be part of stormwater management solutions. However, there is widespread disagreement over funding mechanisms, the community’s responsibilities, and the underlying planning approach to stormwater management. There was no discernable pattern in sector affiliation with any of the narratives. I summarize the dimensionality of stormwater governance and the potential spectrum of ideas about infrastructure, responsibilities, and planning approaches in a framework that characterizes competing viewpoints.